An Investigation into English and Vietnamese Idioms Containing Words Denoting Weather - Đặng Thị Bích Hường (2011)
Idioms are units of language full of problems, especially to second language learners. Therefore, the thesis makes an effort to deal with a small part of idioms: the syntactic and semantic features of English and Vietnamese idioms …..